Improving patient experience in primary care: a multimethod programme of research on the measurement and improvement of patient experience - Jenni Burt; John Campbell; Gary Abel; Ahmed Aboulghate; Faraz Ahmed; Anthea Asprey; Heather Barry; Julia Beckwith; John Benson; Olga Boiko; Pete Bower; Raff Calitri; et al. (NIHR Journals Library, 2017)
Background: There has been an increased focus towards improving quality of care within the NHS in the last 15 years; as part of this, there has been an emphasis on the importance of patient feedback within policy, through National Service Frameworks and the Quality and Outcomes Framework. The development and administration of large-scale national patient surveys to gather representative data on patient experience, such as the national GP Patient Survey in primary care, has been one such initiative. However, it remains unclear how the survey is used by patients and what impact the data may have on practice. Objectives: Our research aimed to gain insight into how different patients use surveys to record experiences of general practice; how primary care staff respond to feedback; and how to engage primary care staff in responding to feedback. Methods: We used methods including quantitative survey analyses, focus groups, interviews, an exploratory trial and an experimental vignette study. Results: (1) Understanding patient experience data. Patients readily criticised their care when reviewing consultations on video, although they were reluctant to be critical when completing questionnaires. When trained raters judged communication during a consultation to be poor, a substantial proportion of patients rated the doctor as 'good' or 'very good'. Absolute scores on questionnaire surveys should be treated with caution; they may present an overoptimistic view of general practitioner (GP) care. However, relative rankings to identify GPs who are better or poorer at communicating may be acceptable, as long as statistically reliable figures are obtained. Most patients have a particular GP whom they prefer to see; however, up to 40% of people who have such a preference are unable regularly to see the doctor of their choice. Users of out-of-hours care reported worse experiences when the service was run by a commercial provider than when it was run by a not-for profit or NHS provider. (2) Understanding patient experience in minority ethnic groups. Asian respondents to the GP Patient Survey tend to be registered with practices with generally low scores, explaining about half of the difference in the poorer reported experiences of South Asian patients than white British patients. We found no evidence that South Asian patients used response scales differently. When viewing the same consultation in an experimental vignette study, South Asian respondents gave higher scores than white British respondents. This suggests that the low scores given by South Asian respondents in patient experience surveys reflect care that is genuinely worse than that experienced by their white British counterparts. We also found that service users of mixed or Asian ethnicity reported lower scores than white respondents when rating out-of-hours services. (3) Using patient experience data. We found that measuring GP-patient communication at practice level masks variation between how good individual doctors are within a practice. In general practices and in out-of-hours centres, staff were sceptical about the value of patient surveys and their ability to support service reconfiguration and quality improvement. In both settings, surveys were deemed necessary but not sufficient. Staff expressed a preference for free-text comments, as these provided more tangible, actionable data. An exploratory trial of real-time feedback (RTF) found that only 2.5% of consulting patients left feedback using touch screens in the waiting room, although more did so when reminded by staff. The representativeness of responding patients remains to be evaluated. Staff were broadly positive about using RTF, and practices valued the ability to include their own questions. Staff benefited from having a facilitated session and protected time to discuss patient feedback. Conclusions: Our findings demonstrate the importance of patient experience feedback as a means of informing NHS care, and confirm that surveys are a valuable resource for monitoring national trends in quality of care. However, surveys may be insufficient in themselves to fully capture patient feedback, and in practice GPs rarely used the results of surveys for quality improvement. The impact of patient surveys appears to be limited and effort should be invested in making the results of surveys more meaningful to practice staff. There were several limitations of this programme of research. Practice recruitment for our in-hours studies took place in two broad geographical areas, which may not be fully representative of practices nationally. Our focus was on patient experience in primary care; secondary care settings may face different challenges in implementing quality improvement initiatives driven by patient feedback. Recommendations for future research include consideration of alternative feedback methods to better support patients to identify poor care; investigation into the factors driving poorer experiences of communication in South Asian patient groups; further investigation of how best to deliver patient feedback to clinicians to engage them and to foster quality improvement; and further research to support the development and implementation of interventions aiming to improve care when deficiencies in patient experience of care are identified. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.